2009
DOI: 10.1007/978-3-642-04438-0_31
|View full text |Cite
|
Sign up to set email alerts
|

A Generalised Model for Distortion Performance Analysis of Wavelet Based Watermarking

Abstract: Abstract.A model for embedding distortion performance for wavelet based watermarking is presented in this paper. Firstly wavelet based watermarking schemes are generalised into a single common framework. Then a mathematical approach has been made to find the relationship between distortion performance metrics and the watermark embedding parameters. The derived model shows that for wavelet based watermarking schemes the sum of energy of the selected wavelet coefficients to be modified is directly proportional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

7
0

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
(9 reference statements)
0
11
0
Order By: Relevance
“…With the introduction of lifting-based wavelet design, lifting-based integer-to-integer Haar transform [8,21] and lifting-based non-linear wavelets [22] have been used in watermarking algorithms. A more comprehensive study on the use of various wavelet kernels in watermarking algorithms can be found at [33,36,37].…”
Section: Wavelet Kernelmentioning
confidence: 99%
“…With the introduction of lifting-based wavelet design, lifting-based integer-to-integer Haar transform [8,21] and lifting-based non-linear wavelets [22] have been used in watermarking algorithms. A more comprehensive study on the use of various wavelet kernels in watermarking algorithms can be found at [33,36,37].…”
Section: Wavelet Kernelmentioning
confidence: 99%
“…At the same time one can decide the minimum modification value for a given coefficient to be modified due to the fact that a greater modification value results in poor imperceptibility and the impact of modification on imperceptibility has been shown in an embedding distortion model in [15]. With the help of this robustness analysis model, it is possible to offer an adaptive watermark weighting parameter which can control the modification value locally along with an effective coefficient selection, so that the guaranteed watermark detection is possible for a given compression ratio with a better imperceptibility.…”
Section: Conditions For Optimisationmentioning
confidence: 99%
“…We aim to specify criteria for choosing coefficients for watermark embedding, that can ensure robustness under various quality scalability adaptations of JPEG2000 encoded bitstreams. Since the imperceptibility is reciprocally related to the robustness, we can use our previous work on the imperceptibility model [15] to find the right balance between these two properties for selecting coefficients for watermark embedding.…”
Section: Introductionmentioning
confidence: 99%
“…The generalisation of our model is evaluated by fitting all major wavelet-based watermarking schemes into a common framework presented in [13]. Initial concepts and the results were reported earlier in the form of conference publications [11,12] while this paper discusses the proposed scheme in detail, introduces non-linear kernels in the analysis and provides exhaustive performance evaluation. The scope of this work is strictly limited to embedding distortion analysis and excludes design and development of new robust watermarking algorithm that considers the derived model.…”
Section: Introductionmentioning
confidence: 99%